Implementing Children's Rights in Vietnamese Families: Cultural and Socioeconomic Influences - Minh Tri Nguyen (Westscience Press, 2024)
Family and family culture are compelling research topics for Social Science researchers. The complexity of this category requires an approach tailored to the research field. In legal science, the family is studied as an entity encompassing relationships regulated by law, such as those between spouses and between parents and children. However, a more practical approach to researching the family from a legal perspective necessitates a general understanding of family culture and its specific impact. As contemporary family culture values continue to evolve, traditional values are sometimes overridden, giving children more autonomy. In this article, we aim to outline the fundamental aspects of family culture and explore the impact of changing family culture on upholding children's rights in Vietnam.